Global imbalances in a world of inflexible real exchange rates and capital controls - Andrew Hughes Hallett; Juan Carlos Martinez Oliva (Asian Development Bank Institute (ADBI), 2011)
This paper addresses the issue of international payments in a stock-flow framework, by capturing the interaction between the current account balance and international assets portfolios of domestic and foreign investors. It is argued that the stability of such interaction may be affected by shifts in the preferences of investors, by the relative rate of return of different assets, and - more in general - by institutional settings. The model is then used for policy analysis purposes to derive the conditions for the existence of dynamic equilibria, and if they can be attained, under the assumption of market-distorting policy choices.
Keywords: F13; F32; F34; 330; Zahlungsbilanzgleichgewicht; Portfolio-Management; Kaufkraftparität; Fester Wechselkurs; Kapitalverkehrspolitik; Kapitalertrag; Volatilität; Zwei-Länder-Modell; Theorie